Climate Change and Infectious Diseases: Evidence from Highly Vulnerable Countries - ANWAR, Asim (Iran J Public Health, 2019)
BACKGROUND: Climate change is an alarming challenge for humanity at large due to its mediating role in emergence and spread of infectious diseases like cholera and malaria. This study was conducted to examine the effect of climate change and some socio-economic factors on incidence of infectious diseases. METHODS: We used country level panel data over the 1990–2017 period using panel ARDL-PMG technique on highly affected countries from climate change. RESULTS: There is a long run co-integrating relationship among climate change, socio-economic factors and prevalence of infectious diseases. Climate change, as measured by the temperature, is contributing to the spread of infectious diseases. CONCLUSION: This is the first study giving evidence of the impact of climate change on incidence of infectious diseases as can be seen from highly vulnerable countries to climate change. It is recommended to improve the level of education along with public health and town planning to reduce the incidence of infectious diseases.